Solvent-free mukaiyama-aldol condensation catalyzed by Ce-Al-MCM-41 mesoporous materials - Kalita, Pranjal; Gupta, Narendra M.; Kumar, Rajiv (Microporous and Mesoporous Materials, 2011)
MCM-41 samples containing Ce4+ and Al3+ in the network, designated as Ce-x-Al-MCM-41 (x = 0.0-0.04), were synthesized and characterized systematically. These samples exhibited higher catalytic activity for Mukaiyama-aldol condensations to produce beta-hydroxy carbonyl compounds under the solvent free conditions, compared to the samples containing either of the two cations. The product yield was found to depend on the electron donating/withdrawing characteristics of reactant molecules being responsible for the observed trend. Series of solvents were also investigated but considerably high yield of aldol products (similar to 95%) could be achieved without using any solvents. In all the cases, the selectivity was found to be 100%, typical of such Mukaiyama-aldol condensations. The higher catalytic activity of Ce-x-Al-MCM-41 is explained on the basis of certain new acid sites generated due to co-incorporation of Ce and Al cations. Published by Elsevier Inc.
Keywords: Acid catalyst; Ce-Al-MCM-41; Silyl enol ether and aldehyde; Silyl ketene acetal